2020
DOI: 10.1097/scs.0000000000007054
|View full text |Cite
|
Sign up to set email alerts
|

Does the Lockdown Influence the Oral and Maxillofacial Surgery Service in a Level 1 Trauma Hospital During the COVID-19 Pandemic?

Abstract: The pandemic status of the Novel Coronavirus 2019 has affected many countries around the world, due to the high virulence of the SARS-CoV-2, the recommended protocol to prevent infection is social isolation. The purpose of this study was to compare the number of patients admitted and their epidemiological data on a Level 1 Trauma Hospital after the declaration of the pandemic status and the first week of mandatory lockdown, with the same period of time in the last year. This was a retrospective study of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Interestingly, the reduction of 66.7 % in facial surgical activity observed in our hospital matched those described in other Western European countries: -65.5 % in France 9 , -69.1 % in Italy 10 and -71.4 % in the United Kingdom 11 . In contrast, reduction of surgical activity in Brazil and USA ranged only from -27.5 % to -52.3 % when compared to the equivalent period of the previous one or two years [12][13][14] .…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the reduction of 66.7 % in facial surgical activity observed in our hospital matched those described in other Western European countries: -65.5 % in France 9 , -69.1 % in Italy 10 and -71.4 % in the United Kingdom 11 . In contrast, reduction of surgical activity in Brazil and USA ranged only from -27.5 % to -52.3 % when compared to the equivalent period of the previous one or two years [12][13][14] .…”
Section: Discussionmentioning
confidence: 86%
“…On January 2020, WHO (World Health Organization) declared it an "infectious disease pandemic" after thousands of cases were reported across the world [14]. The universal wearing of face masks and physical or social distancing [15,16] is safeguarding the world population. This is because the mode of transmission of COVID-19 is airborne, as the viral particles are shed from the nose and mouth of asymptomatic and infected person through respiratory droplets [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a study from Brazil, the authors questioned if the lockdown during pandemic influenced the oral and maxillofacial surgery services? 6 They found a 52.27% decrease in the total number of patients and a 76.34% decrease in the total consultations of the service of oral and maxillofacial surgery during the lockdown. They concluded that the lockdown was an effective way to reduce the transmission of the COVID-19, the hospital usage, and occupation.…”
mentioning
confidence: 95%